Altered Morphologies and Functions of the Olfactory Bulb and Hippocampus Induced by miR-30c - Sun, Tingting; Li, Tianpeng; Davies, Henry; Li, Weiyun; Yang, Jing; Li, Shanshan; Ling, Shucai (Frontiers in Neuroscience, 2016)
Adult neurogenesis is considered to contribute to a certain degree of plasticity for the brain. However, the effects of adult-born neurons on the brain are still largely unknown. Here, we specifically altered the expression of miR-30c in the subventricular zone (SVZ) and dentate gyrus (DG) by stereotaxic injection with their respective up-and down-regulated lentiviruses. Results showed an increased level of miR-30c enhanced adult neurogenesis by prompting cell-cycles of stem cells, whereas down-regulated miR-30c led to the opposite results. When these effects of miR-30c lasted for three months, we detected significant morphological changes in the olfactory bulb (OB) and lineage alteration in the hippocampus. Tests of olfactory sensitivity and associative and spatial memory showed that a certain amount of adult-born neurons are essential for the normal functions of the OB and hippocampus, but there also exist redundant newborn neurons that do not further improve the functioning of these areas. Our study revealed the interactions between miRNA, adult neurogenesis, brain morphology and function, and this provides a novel insight into understanding the role of newborn neurons in the adult brain.